An investigation on the feasibility of the use of dry floor system for low cost construction - Abdullah, Redzuan; Abd. Hamid, Hazlan (Universiti Teknologi Malaysia, 2006)
Construction and property industry is a very important component of Malaysian economy. It spawns 126 sub?industries and contributing about 24% of the country Gross Domestic Product (GDP). Malaysian housing industry mass?produces more houses on per capita basis than any other country in the world. Despite highly dynamic and important economic sector, building construction in Malaysia is still at the bottom rung of the building technology ladder. Most of the Malaysian construction practices for low rise buildings such residential and shop lots today still use conventional methods such as reinforced concrete and brick works. The conventional methods are inefficient, dull, dirty, dangerous, low quality, noisy, disruptive and environmentally unfriendly. It is also labor intensive. As a consequence, huge numbers of foreign labors are lured into the country. The influx of too many foreign labors may cause rising social problems. Economically, labor cost is not forever cheap. Time will come when the labor cost and land speculation will combine to price the average Malaysian families out of house and property ownership. Industrialized Building System (IBS) is being promoted by the Construction Industry Development Board (CIDB) of Malaysia as an alternative to the conventional construction method. The IBS approach to construction is very efficient and non?labor intensive. As such, implementation of IBS not only competitive, but also can reduce the dependency on foreign labors. Other benefits of IBS include minimal wastage, efficient, tidier and safer worksites, better quality control, faster project completion, and lower total construction costs.